2017
DOI: 10.1007/s10841-017-9968-0
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of Regal Fritillary (Speyeria idalia) habitat utilizing biological monitoring data along the big bend of the Platte River, NE

Abstract: Viola sororia and very moderate management regimes that remove shrubby cover (negatively associated) and promote forb cover (positively associated), while providing ample recovery time on burned and grazed patches for litter development (positively associated). Random forest analysis describes the presence of V. sororia, percent forb cover, and habitat isolation as the top three habitat variables of importance in predicting the presence/absence of S. idalia. Our finding that habitat isolation is a major predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 46 publications
(119 reference statements)
3
36
0
Order By: Relevance
“…Previous research has even suggested that regal larvae perish in the absence of litter accumulation, possibly from exposure (Wagner et al 1997, Ferster andVulinec 2010). These results coincide with a number of other studies that indicate litter buildup is an important component to regal habitat (Mason 2001, Davies et al 2007, Powell et al 2007, Vogel et al 2007, Ferster and Vulinec 2010, Helzer 2012, Caven et al 2017. These results coincide with a number of other studies that indicate litter buildup is an important component to regal habitat (Mason 2001, Davies et al 2007, Powell et al 2007, Vogel et al 2007, Ferster and Vulinec 2010, Helzer 2012, Caven et al 2017.…”
Section: Habitat Characteristicssupporting
confidence: 85%
See 4 more Smart Citations
“…Previous research has even suggested that regal larvae perish in the absence of litter accumulation, possibly from exposure (Wagner et al 1997, Ferster andVulinec 2010). These results coincide with a number of other studies that indicate litter buildup is an important component to regal habitat (Mason 2001, Davies et al 2007, Powell et al 2007, Vogel et al 2007, Ferster and Vulinec 2010, Helzer 2012, Caven et al 2017. These results coincide with a number of other studies that indicate litter buildup is an important component to regal habitat (Mason 2001, Davies et al 2007, Powell et al 2007, Vogel et al 2007, Ferster and Vulinec 2010, Helzer 2012, Caven et al 2017.…”
Section: Habitat Characteristicssupporting
confidence: 85%
“…Regals are commonly described as a prairie-specialist, indicator, or flagship species of pristine prairie habitat in the literature (Hammond and McCorkle 1983, Swengel 1996, Moranz et al 2014, Henderson et al 2018. In fact, big bluestem has been positively associated with regals and documented to be nearly twice as abundant on plots where regals were present vs. plots where they were absent (Caven et al 2017). Previous studies have reported similar findings regarding the importance of native grass species and lack of woody vegetation to regals.…”
Section: Habitat Characteristicsmentioning
confidence: 77%
See 3 more Smart Citations